“Why So Heteronormative?”: A Multimodal Analysis of GBV Representations in Campaign and Advocacy Materials - Deocampo, Irish Joy G. (Review of Women's Studies, 2024)
While the Philippines continues to be recognized as one of the LGBTQIA+-friendly countries globally,cases of gender-based violence (GBV) against members of the LGBTQIA+ community continue to raise concern. However, mainstream discourse around gender-based violence is dominantly defined by the male-perpetrator-female-victim narrative. I argue that a heteronormative conceptualization of GBV leads to the exclusion of LGBTQIA+ experiences and other forms of GBV that do not fall under this category. Current campaign materials against GBV provide a more expansive representation of GBV.This study is concerned with investigating these materials and analyzing how these new iterations possibly challenge or reinforce heteronormative constructions of GBV. I analyzed four selected posters that included LGBTQIA+ identities using multimodal discourse analysis. My findings revealed that, while there is a considerable attempt to include members of the LGBTQIA+ community in the GBV discourse through representation, the materials reproduce harmful stereotypes about GBV, women, and members of the LGBTQIA+ community. Stereotypes include hypersexualization, revictimization, and stigmatization of victims. I suggest that the process of producing these posters be reviewed and a more participatory framework be adopted in the future. I also strongly recommend the legalization of the Anti-Discrimination Bill to strengthen the campaign against GBV.